Correct type designation of the Linnaean name Satureja graeca, basionym of Micromeria graeca (Lamiaceae) - Ferrer-Gallego, Pedro Pablo; Senar, Romà; Laguna, Emilio (Phytotaxa, 2019)
Some aspects concerning the typification of the Linnaean name Satureja graeca, basionym of Micromeria graeca (Lamiaceae) are discussed. This name had previously been “typified” by Siddiqi in 1985 from a specimen kept at LINN, and also later by Morales in 1991 from another specimen preserved in the same Linnaean herbarium. However, it is not sure that these specimens are part of Linnaeus’s original material so neither cannot be considered a lectotype. An illustration published by Morison in 1699 and cited by Linnaeus in the protologue of Satureja graeca is designated as the lectotype of the name.